Novel orlistat LDL-like nanoparticles as potential anti-cancer medicines - Bebawy, George (2022)
Objectives: The field of Nano-therapeutics has gained vast attention over the past decades, described as the future cancer medicine. Controlling the particle size is highly crucial for many reasons including proper drug formulation, tumour targeting and enhancing bioavailability. Mostly, nanoparticles within the range of 100 to 200 nm are the most easily manufactured, yet they may not be the best option for optimum drug targeting and tissue accumulation which are in favour of smaller particles (< 50nm). Thus, preparing nanoparticles of small size (<50nm) in an easy way and with high concentrations of the required drug still requires work.